Psychological impact of COVID-19 among frontline financial services workers in Bangladesh. (3rd July 2021) - Rana, Rezwanul Hasan; Islam, Ariful
Abstract: The COVID-19 pandemic has affected millions of people worldwide both physically and mentally. In resource-strapped countries, high levels of psychological distress caused by fear of getting infected with the deadly disease has been observed in densely populated communities and among frontline workers (e.g., healthcare workers and retail employees), who provide services without wearing the appropriate personal protective equipment. This study assessed the level of psychological distress among bank employees, who are also essential frontline workers. Data were collected from 120 bank employees by using a predesigned survey questionnaire consisting of Kessler Psychological Distress Scale (K10) questions. Nine out of ten respondents indicated that they were likely to experience mild to severe psychological distress, and 86.6% felt vulnerable to having close contact with a carrier of the rapidly spreading COVID-19 virus. The Chi-square test results indicated that married employees (36.37 vs 32.16) and those assigned in bank branches (36.34 vs 33.25) had a higher likelihood of experiencing psychological distress than those who were not married and those assigned in head offices, respectively. To address this issue, health policymakers and bank regulatory authorities must develop mental health interventions, treatments, and guidelines specific for bank employees.